2018
DOI: 10.1039/c7tx00288b
|View full text |Cite
|
Sign up to set email alerts
|

Case examples of an evaluation of the human relevance of the pyrethroids/pyrethrins-induced liver tumours in rodents based on the mode of action

Abstract: The CAR-mediated MOA for liver tumorigenesis is of no carcinogenic risk for humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 83 publications
(194 reference statements)
1
19
0
Order By: Relevance
“…EPA 2000). Mitogenicity via constitutive androstane receptor (CAR) and PPARa are considered key components of the MOA for hepatocyte tumorigenicity in the rodent model; CYP2B and CYP4A are well-documented biomarkers for CAR and PPARa activation (Corton et al 2014;Corton, Peters, and Klaunig, 2018;Lake 2018;Yamada 2018). Female CD-1 mice exposed to feed containing 5,000 ppm (780-807 mg/kg/day) of permethrin for 52 weeks exhibited marked increases in hepatocellular microsomal enzyme activity that included a 142% to 283% increase in CYP, CYP1A, CYP2B, CYP2E1, and CYP3A2 as well as a 3-fold increase (829%) in CYP4A induction, relative to controls (U.S. EPA 2000).…”
Section: Discussionmentioning
confidence: 99%
“…EPA 2000). Mitogenicity via constitutive androstane receptor (CAR) and PPARa are considered key components of the MOA for hepatocyte tumorigenicity in the rodent model; CYP2B and CYP4A are well-documented biomarkers for CAR and PPARa activation (Corton et al 2014;Corton, Peters, and Klaunig, 2018;Lake 2018;Yamada 2018). Female CD-1 mice exposed to feed containing 5,000 ppm (780-807 mg/kg/day) of permethrin for 52 weeks exhibited marked increases in hepatocellular microsomal enzyme activity that included a 142% to 283% increase in CYP, CYP1A, CYP2B, CYP2E1, and CYP3A2 as well as a 3-fold increase (829%) in CYP4A induction, relative to controls (U.S. EPA 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, a number of nongenotoxic chemicals which are CAR activators have been shown to produce liver tumors in the mouse and/or rat. Robust MOAs have been established for these compounds, which have similar key and associative events to those identified for PB (Holsapple et al 2006;Lake 2009Lake , 2018Cohen 2010;Elcombe et al 2014;Yamada 2018).…”
Section: Moa For Rodent Liver Tumor Formation By Pb and Other Car Activatorsmentioning
confidence: 93%
“…However, this does not mean that effects of CAR activators on hepatocyte RDS in rodent liver are only transient, that is, an increase in the rate of hepatocyte RDS is only observed after short-term treatment with CAR activators. As Cabral et al (1979), Kolaja et al (1996), Stevenson et al (1999) Kostka et al (1996), Kiyosawa et al (2008), Kazantseva et al (2013), Harada et al (2016) Cunningham et al (1994), Griffin et al (1995Griffin et al ( , 1996, and Parkinson et al (2006) Piperonyl butoxide Goodman et al (2000) and Wang et al (2015Wang et al ( , 2017 Triadimefon All of these compounds have been shown to have a MOA for rodent liver tumor formation similar to that described for PB (Cohen 2010;Elcombe et al 2014;Lake 2018;Yamada 2018), with data required to establish a CAR activation MOA for rodent liver tumor formation being obtained as described in the text.…”
Section: Car-dependent Hepatocyte Proliferationmentioning
confidence: 94%
“…For interpreting findings from the hCAR and hCAR/hPXR mice, it should be noted that in these transgenic mouse models, the human receptor(s) operate in a mouse hepatocyte environment. The downstream genes acted upon by CAR are those of the mouse, not humans 5,27,29,85 , indicating that the findings from hCAR and hCAR/hPXR mice do not appropriately reflect human responses. Towards better understanding of these controversial findings, it is very important to evaluate the effects of PB on human hepatocyte proliferation in a chimeric mouse model in which human receptor(s) operate in a human hepatocyte environment.…”
Section: Studies In Cultured Human Hepatocytesmentioning
confidence: 99%
“…As shown in Table 1, uPA/SCID mice were employed for the evaluation of PB 19 , and in subsequent investigations, the cDNA-uPA/SCID mouse model has been used in studies with metofluthrin and momfluorothrin 20 . Metofluthrin and momfluorothrin are pyrethroid insecticides that induced liver tumors in rats with CAR-mediated MOA 27,[62][63][64] . Previous studies with cultured hepatocytes have demonstrated that metofluthrin 65,66 and momfluorothrin 20 increased rat hepatocyte RDS, but not in human hepatocytes, which is strongly consistent with the results of PB.…”
Section: Studies In Chimeric Mice With Human Hepatocytes (Pxb Mouse)mentioning
confidence: 99%